Arius kesslerl and amp; sciadeops troschelii (pisces: ariidae) growth in floating net cages in estuarine waters of buenventura bay-colombia (1999)
Two species of estuary catfish the Arius kessleri (CoCoCo) and the Sciadeops troschelii (Nato) were held in floating net cages at varying densities in estuarine waters of Buenventura Bay-Colombia. After 120 days for the Cococo had weights of 84.1 g Y64 g with densities of 5 and 30 specimen/rn'. The growth average was 0.58-0.39 g/day; the net yield obtained vary from 0.35 to 1.16 Kg/m', the food conversion ratio vary from 3.3 to 5.0 and de survival rate vary from 86% to 100%. With the Nato we obtained weights of 164 and 184 g, beginning with weights of 41 and 108 g their growth average vary from 0.50 to 0.82 g/day. The net yield obtained vary from 0.58 to 0.75 Kg/m' and the survival rate vary from 83% to 100%. From these results we conclude that the two species of catfish studied are strong species but they do not offer good possibilities for fish farming in estuarine waters.